Pelatihan Pembuatan Jaringan LAN pada Siswa SMK Telkom Kendari - Lestari Puput P; Fitriani H; Pratiwi Tiwi B; Samusu Samusu; Muhammad Sabirin (LP3M, Universitas Muhammadiyah Kendari, 2021)
The aim of this civil service is to find out to what extent the students understand the basic topics of cable crimping and network design. This community service provides understanding, understanding, compiling, and using computer network simulation software (packet tracer) as well as training in cable crimping and testing of local area network (LAN) based computer networks. The network simulation community service method used is the experimental and design method, and is carried out in a group, pre-test and post-test design. The results of this community service were carried out in 2 sessions as well as in the supervision of carrying out activities with direct practice and carrying out reflective activities aimed at the level of understanding that the students had after holding the training. This was evident from the treatment of the students in conducting LAN testing practices in the network, where 25 students who completed the exercise were declared successful or 100% capable of conducting local area network tests by 25 students.